Emerging non-PCV13 serotypes of noninvasive Streptococcus pneumoniae with macrolide resistance genes in northern Japan. (January 2016) - Kawaguchiya, M.; Urushibara, N.; Aung, M.S.; Morimoto, S.; Ito, M.; Kudo, K.; Sumi, A.; Kobayashi, N.
Abstract: In Japan, the 7-valent pneumococcal conjugate vaccine (PCV7) was introduced to the nation's routine immunization program in April 2013 and was replaced by the 13-valent pneumococcal conjugate vaccine (PCV13) in November 2013. Distribution of serotypes and macrolide resistance genotypes was investigated for a total of 1097 (975 children, 122 adults) and 960 (873 children, 87 adults) clinical isolates of Streptococcus pneumoniae from noninvasive infections in Hokkaido (northern main island of Japan) in the routine immunization periods for PCV7 and PCV13 (April–October 2013 and November 2013–November 2014, respectively). Serotype was determined by sequential multiplex PCR and additional genetic analyses. Macrolide resistance genes erm (B) and mef (A/E) were detected by multiplex PCR. Although the most prevalent serotypes in children were 23A and 6C in the PCV7 period, after replacement with PCV13, 19A became the most common, followed by 6C, 15A and 23A. Among adults, serotype 3 was consistently the most frequent throughout the study periods. Compared with values from the pre-PCV7 routine immunization period, PCV7 serotypes decreased from 48.3 to 3.3% in the PCV13 period among children, while the rates of non-PCV13 serotypes (particularly 15A, 23A, 11A, 10A and 35B) increased from 39.7 to 75.1% (p < 0.001). In the PCV13 period, erm (B), mef (A/E) and both of these genes were detected in 75.8, 31.6 and 11.3% of all isolates, respectively. Serotype 19A accounted for 76.9% of the isolates with both the macrolide resistance genes, and emerging non-PCV13 serotypes 15A, 15C and 23A mostly harboured erm (B).